Pengaruh Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi di Kabupaten Jayapura Tahun 2010–2023 - Ida Ayu Purba Riani (Universitas Cenderawasih, 2025)
Growth (Ln GDRP) in Jayapura Regency during the period 2010–2023. HDI is a human development indicator that reflects quality of life in terms of education, health, and purchasing power, while GRDP is used as an indicator of regional economic growth. The method used in this research is quantitative analysis with a semi-log regression approach in the Log-Lin form. The analysis results show that HDI has a positive and significant effect on economic growth. The regression coefficient for HDI of 0.1651 indicates that every one-point increase in HDI will increase economic growth by 0.1651%. The R-squared value of 0.9765 shows that 97.65% of the variation in economic growth (Ln GRDP) can be explained by variations in HDI, indicating a very high explanatory power of the model. Further statistical tests confirm the significance of these results. The t-statistic value for HDI is 22.3322 with a probability of 0.0000, indicating a highly statistically significant effect. Similarly, the F-statistic test with a value of 498.7262 and a probability of 0.0000 indicates that the model as a whole is significant in explaining the relationship between the variables. The implications of these findings reinforce the crucial role of human development in driving economic growth. Improvements in HDI, which include health, education, and living standards, have proven to significantly contribute to economic growth. These findings provide an empirical basis for policymakers to prioritize programs that enhance the quality of life of the population, as such efforts are not only socially beneficial but also promote economic progress. Keywords: Human Development Index, Economic Growth, Log-linear Regression